(untitled) (Research, Society and Development, 2023)
Objective: This study seeks to identify in the literature scientific and relevant information about breast cancer in older women, as well as how it has contributed to the improvement of nursing practice and public self-care. Methodology: This is na exploratory Integrative Literature Review (ILR) about breast cancer in older women in nursing in the last five years. Articles were chosen through the Virtual Health Library, and electronic data bases of BDENF, LILACS, Medline and (DeCS). Outcome: The articles examined show a variety of reports and experiences by authors on the theme: Breast cancer in the elderly. The years with the most evidence of these articles being published in scientific journals were 2021 and 2022. Five (5) articles were chosen from the Lilacs database; three (3) articles were found in the Virtual Health Library; and one (1) article was chosen based on BDENF data. Conclusion: It is concluded that the various writings examined are extremely important, as is the on going discussion on the subject. This study may help nurses in training and those who are already trained under stand where, how to access, and how to use search tools.